Passive micro-optical alignment methods - Boudreau, Robert A. (CRC Press, 2005)
Optical alignment is the most expensive step in manufacturing micro-optical components and fiber optics, but here contributors from companies in the US, Europe, and Japan describe a new low-cost approach known as passive alignment, which is just beginning its migration from the laboratory bench to the production line. They present various mechanical and optical methods that allow the micro-optics to be positioned and bound without having to power the device being manufactured. They also review utilities for passive alignment. Among specific topics are soldering technology for opto-electronic packaging, a low-cost plastic packaged module, and the Monte Carlo analysis of passive alignment methods.